Pemindahan Depo Pertamina Plumpang: Antara Politik atau Hukum? - Kurniawan, Felix Alexander; Aripin, Jacqueline; Aristo, Erly (Magister Kenotariatan Universitas Surabaya, 2024)
Legal issues in Indonesia are often dominated by political considerations, frequently sidelining fundamental legal principles. Decisions made by law enforcement authorities in Indonesia are often politically motivated, resulting in populist policies. One such case involves the relocation of the Depo Pertamina Plumpang in North Jakarta, impacting the residents of Tanah Merah. Although various legal instruments have been provided to the residents of Tanah Merah, they fundamentally lack legitimate ownership of the land. This study examines the legal and political aspects of the Depo Pertamina Plumpang relocation. The research employs a normative legal method, incorporating statutory and conceptual approaches, with primary legal sources and materials. The findings reveal that the legal politics underlying the relocation of the Depo Pertamina Plumpang serve to grant legitimacy for the residents of Tanah Merah to establish residential buildings. However, this has led to populist policies that conflict with the legality of land and property ownership. Specifically, the Temporary Area Building Permits (IMB Kawasan Sementara) issued by the government are legally invalid and cannot constitute a basis for land ownership. As land ownership is authenticated through land title certificates, the actions taken result in the residents of Tanah Merah occupying hazardous areas within the buffer zone, further exacerbating the risks associated with these settlements. 4o Keywords: Politik Hukum, penegakan hukum, Depo Pertamina Plumpang.